Risk stratification of chronic liver disease in the community - Harris, Rebecca (2019)
Introduction There is an appreciable undiagnosed burden of Chronic liver disease within our society with mortality rates increasing over recent decades. The reasons for this include the rise in lifestyle related risk factors (e.g. hazardous alcohol use, type 2 diabetes and obesity), the asymptomatic nature of the disease which ensures patients do not present to a clinician at an early stage, and the ineffectiveness of current diagnostic tests available to primary care physicians.